Changes of Japanese Marxist Economic Thoughts in Post-War - Cao, Xi (Transactions on Social Science, Education and Humanities Research, 2023)
After the Second World War, Japanese Marxist economic thoughts was recovered and made great development, gradually forming four schools of "Orthodox", "Uno", "Civil Society" and "Mathematical Economics". According to the focus of different periods and the characteristics of the historical background, it can be divided into the recovery period in the early stage after the war, the trough period after the revolutions of 1989 in the Soviet Union and the stability period since the bubble economy.